Hydrologic and Landscape Controls on Dissolved Organic Matter Composition Across Western North American Arctic Lakes. Issue 1 (30th December 2022) - Kurek, Martin R.; Garcia‐Tigreros, Fenix; Wickland, Kimberly P.; Frey, Karen E.; Dornblaser, Mark M.; Striegl, Robert G.; Niles, Sydney F.; McKenna, Amy M.; Aukes, Pieter J. K.; Kyzivat, Ethan D.; Wang, Chao; Pavelsky, Tamlin M.; et al.
Abstract: Northern high‐latitude lakes are hotspots for cycling dissolved organic carbon (DOC) inputs from allochthonous sources to the atmosphere. However, the spatial distribution of lake dissolved organic matter (DOM) is largely unknown across Arctic‐boreal regions with respect to the surrounding landscape. We expand on regional studies of northern high‐latitude DOM composition by integrating DOC concentrations, optical properties, and molecular‐level characterization from lakes spanning the Canadian Taiga to the Alaskan Tundra. Lakes were sampled during the summer from July to early September to capture the growing season. DOM became more optically processed and molecular‐level aromaticity increased northward across the Canadian Shield to the southern Arctic and from interior Alaska to the Tundra, suggesting relatively greater DOM incorporation from allochthonous sources. Using water isotopes (δ 18 O‐H2 O), we report a weak overall trend of increasing DOC and decreasing aromaticity in lakes that were hydrologically isolated from the landscape and enriched in δ 18 O‐H2 O, while within‐region trends were stronger and varied depending on the landscape. Finally, DOC correlated weakly with chromophoric dissolved organic matter (CDOM) across the study sites, suggesting that autochthonous and photobleached DOM were a major component of the DOC in these regions; however, some of the northernmost and wetland‐dominated lakes followed pan‐Arctic riverine DOC‐CDOM relationships, indicating strong contributions from allochthonous inputs. As many lakes across the North American Arctic are experiencing changes in temperature and precipitation, we expect the proportions of allochthonous and autochthonous DOM to respond with aquatic optical browning with greater landscape connectivity and more internally produced DOM in hydrologically isolated lakes. Plain Language Summary: As the Arctic responds to warming, permafrost thaw, and variations in precipitation, the distribution of carbon pools within northern high‐latitude lakes will also change. Specifically, the composition of dissolved organic matter (DOM) and how it is altered and moved from the landscape to the atmosphere will be highly dependent on local precipitation patterns and hydrology, but these relationships are not well constrained across large regions. We sampled over 70 individual lakes during the summer spanning various ecoregions from interior Canada to the Alaskan Tundra and characterized their dissolved organic carbon (DOC) concentrations and DOM composition using bulk and molecular‐level analysis. Overall, DOM from these lakes was highly influenced by aquatic primary production but increased in the relative proportion of terrestrially derived organic matter as lake setting transitioned from forests to shrublands above the tree line. We also report a weak relationship between increasing DOC and decreasing terrestrial DOM as lakes become more hydrologically isolated across the pan‐Arctic; however, regional trends were stronger within forested sampling areas and weaker in shrublands. With the hydrologic setting of many northern high‐latitude lakes predicted to change in the coming decades, we expect the proportions of land‐ and aquatic‐derived DOM to respond as well. Key Points: Dissolved organic matter in high‐latitude Canadian lakes increases in aromaticity northward as forests transition to shrublands High‐latitude lakes that are hydrologically connected to the landscape have lower dissolved organic carbon (DOC) and are more allochthonous than isolated lakes DOC in many northern high‐latitude lakes was influenced by autochthonous production and correlated weakly with absorbance